1992
DOI: 10.1002/ijc.2910510209
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐restricted responses of CD8+ AND CD4+ T‐cell clones from regional lymph nodes of melanoma patients

Abstract: Regional lymph-node (LN) lymphocytes may constitute an important defence against the spread of human melanoma beyond regional LNs. The present study was directed to clonal analysis of lymphocytes cultured either directly from the LNs or after stimulation in cultures with autologous melanoma (MLTC). T-cell clones derived from MLTC reactions had either CD4+ or CD8+ phenotypes. Inhibition studies with monoclonal antibodies (MAbs) suggested that the CD8+ cytotoxic T-cell (CTL) clones had MHC-class-I-restricted cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The latter studies suggest that CD4 T cells may exert direct cytotoxic effects on melanoma cells separate from their helper effects on CD8 CTLs. This is supported by several studies showing that CD4 T cells mediate direct lytic effects on melanoma cells in vitro (Chen and Hersey, 1992;Takahashi et al, 1995) and that an epitope in tyrosinase is one of the antigens recognized by CD4 T cells (Topalian et al, 1996).…”
mentioning
confidence: 70%
“…The latter studies suggest that CD4 T cells may exert direct cytotoxic effects on melanoma cells separate from their helper effects on CD8 CTLs. This is supported by several studies showing that CD4 T cells mediate direct lytic effects on melanoma cells in vitro (Chen and Hersey, 1992;Takahashi et al, 1995) and that an epitope in tyrosinase is one of the antigens recognized by CD4 T cells (Topalian et al, 1996).…”
mentioning
confidence: 70%
“…Although experimental immunization strategies for patients with melanoma and other cancers currently emphasize shared class I-restricted tumor antigens recognized by CD8+ T cells, immunization against both class I-and class II-restricted epitopes may increase the effectiveness of these approaches. Previous reports suggesting the presence of shared MHC class II-restricted melanoma antigens have measured direct T-cell-tumor cell interactions and were thus limited by the extensive polymorphism of human class II molecules and reagent availability (39)(40)(41)(42). However, as demonstrated here, a bioassay which utilizes one APC for multiple sources of antigen will permit rapid screening and detection of shared CD4-recognized tumor antigens.…”
Section: Methodsmentioning
confidence: 92%
“…However, high background activities and wide variability among replicate samples sometimes make these assays difficult to interpret. Several recent reports have shown the feasibility of using prolonged (12)(13)(14)(15)(16)(17)(18) h) 51Cr release assays to assess CD4+ T cell responses to autologous melanoma cells. '12,14,22' Paradoxically, two studies have shown that cytolytic antimelanoma CD4+ cells are MHC class I restricted but not class II restricted.…”
Section: Assessment Ofallogeneic Melanoma Recognitionmentioning
confidence: 99%